A Method to Design Weather-Responsive Speed Limit Subject to Visible Distance in the Absence of Road Surface Friction Coefficient - Yuan Jian-Hua; Wu Yang; Ma Qing; Zhang Zhiyong (2015 8th International Conference on Intelligent Computation Technology and Automation (ICICTA), 2015)
The popular weather-responsive design of variable speed limit (VSL) of freeway subject to visible distance relys on technically expensive detection/estimation of friction coefficient, not applicable for economy-underdeveloped areas. A method is proposed to design weather-responsive VSL at lower cost, using equivalently-transformed four discrete thresholds of friction coefficient contingent on different types and intensities of adverse weather (including: the road surface conditions of dry or wet, and the conditions of water or snow/ice covering adhered onto road surface), instead of expensive real time-detected continuous spectrum of friction coefficient.